Corrosion effects on pullout behavior of hooked steel fibers in self-compacting concrete - Frazão, Cristina Maria Vieira (2016)
Steel fibers are used in concrete to improve its mechanical properties, such as postcracking load bearing capacity and energy absorption performance, and also to limit the crack width, with beneficial consequences of concrete durability. Steell fiber reinforced concrete (SFRC) structures are subjected to chloride and carbonation penetration that can initiate corrosion of steel fibers, with eventual pernicious consequences of structural and durability performance. Cracks in concrete are known to fasten initiation of steel corrosion in reinforced concrete structures. The investigation of the impact of cracks on the corrosion initiation and the associated interfacial damage between concrete and steel fibers is important for understanding the mechanical behavior of SFRC. In the present work, the corrosion action on the mechanical behavior of cracked Steel Fiber Reinforced Self-Compacting Concrete (SFRSCC) was investigated. For this purpose, an experimental program was performed to characterize the corrosion of hooked-end steel fibers, and to assess the fiber pullout behavior in cracked concrete, previously subject to the action of corrosion by exposure to aggressive chloride environment. The results revealed that the susceptibility to corrosion of steel fibers that cross a pseudo-crack increased with the crack width, but the corrosion products in the fiber-matrix interface can increase the fiber pullout strength in cracked SCC at least up to a certain limit of crack width.